Principal Component Analysis of Quantitative and Qualitative Traits in Sixty Mung Bean (Vigna radiata L. Wilczek) Genotypes - Nalajala, Sindoora; Muniyandi, Samuel Jeberson; Manjunath, P. (International Journal of Bio-resource and Stress Management, 2023)
The present study was conducted at Genetics and Plant breeding plot, Central Agricultural University in July 2021−August 2022, sixty mung bean genotypes were evaluated for 28 morphological quantitative and qualitative traits planted in RBD with three replications. Among traits, 14 were yield and its attributing traits and other 14 were qualitative characters scored according to IBPGR guidelines of mung bean. Principal component analysis (PCA) was done to identify the significant characters and the variation of genotypes based on different traits. Principal Component Analysis revealed that out of 28, only first nine principal components exhibited more than 1.0 eigen value and showed about 71.22% total variability. PC1 showed 19.42% variability with eigen value 5.44, and was dominated by traits i.e., plant height (0.496), number of clusters plant-1 (0.762), number of pods plant-1 (0.868), number of seeds pod-1 (0.409), number of seeds plant-1 (0.933), biological yield (0.905) and seed yield plant-1 (0.878), which concludes it as a yield attributing principal component. PC 1 and PC 9 accounts for yield contributing traits, PC 6 accounts for seed characters, PC 2 for duration and all the remaining PCs for different qualitative characters. Based on the PC scores in PC 1 and PC 9 which are yield attributing components the genotypes namely SML 1115(8.7), IPMD 1604(6.93), IPM 1103-1(9.58) PM 1624(8.08), RMG 1132(10.27), Virat (IPM 205-7) (7.42), IPM 1603-1(9.77) and MML 2568(7.77) were selected for high yield and its attributing traits.